Conceptual Analysis of Empathy in the Gracious Qur’an - Iman Sayyid Moharrami; Abolfazl Ghaffari (آموزه‌های قرآنی, 2022)
The present study has a different view of the concept of empathy as one of the life skills and has examined the path of empathy growth and development, which can lead to the perfection of empathy, i.e. the sacrifice (Arabic: ایثار, Romanized: Īthār, altruism, self-sacrifice). The views of the Holy Quran and the views of Quranic scholars and psychologists on empathy were collected to achieve this goal, and examined using conceptual analysis. The results showed that empathy is semantically related to the concepts of compassion (condolence), open-handed (the quality of being munificent), generosity, infāq (Arabic: إنفاق, disbursement) iḥsān (Arabic: إحسان ʾiḥsān, benefaction), and the sacrifice (self-sacrifice) in Islamic texts. The sacrifice (self-sacrifice) is one of the most important concepts related to empathy, which is the highest empathy. The sacrifice (self-sacrifice) is a valuable word that comes and derives from empathy. These items in order to move from empathic behaviors toward sacrifice are suggested: Islamic education (cultivation), purification from negligence, soul (psyche, spirit) harms and moral degradation (ugliness), strengthening softness of heart, challenging negative imaginations about self-sacrifice, teaching skills and moral attributes related to self-sacrifice, modeling, understanding the truth of God and strengthening the relationship with God.